Desenvolvimento de planilha em Excel para dimensionamento de instalação elétrica de usina fotovoltaica de minigeração distribuída - Nobre, Raíssa Carneiro (2024)
During the specification of electrical components for photovoltaic power plants of distributed mini-generation, it is necessary to manage a large volume of data, ranging by requirements requested from the Brazilian Standards to project criteria adopted arbitrarily and limitations requested by the commercial availability of the electrical components expected in the project. In addition to performing this management, it is up to the designer to explore different arrangements for the installation to ensure that the best possible solution is implemented, meeting all the requirements defined by the project scope. It is also necessary that this specification process is carried out in the shortest possible time to achieve significant productivity and fit the high current demand for this type of project. By referring to the literature on low and medium voltage electrical installations as well as photovoltaic systems, it is possible to understand the calculations and decision-making processes that must be carried out during the aforementioned specification. However, it is necessary to relate these processes and coordinate them with the requirements that must be fit in the specification of the electrical components of the installation, to obtain results that comply with these requirements. Therefore, this work presents the development of a spreadsheet in Excel software, which aims to completely perform the calculations and decision-making inherent to the previously mentioned specification process. The spreadsheet automatically considers all normative requirements and project criteria specified for the adopted context, in a significantly shorter time than that required by manual methods to perform the same task. Based on comparative tests conducted, this work concluded that the specification performed through the developed spreadsheet provides reliable results in 10% of the time required to perform the same procedure manually, indicating that the tool in question is indeed effective for greater productivity in the design of photovoltaic power plants for distributed mini-generation.